2010
DOI: 10.1577/t09-227.1
|View full text |Cite
|
Sign up to set email alerts
|

Predation on Early Life Stages of Lake Sturgeon in the Peshtigo River, Wisconsin

Abstract: Mortality of early life stages can limit recruitment of fishes, and understanding the impacts of various sources of mortality has long been a goal of fisheries management. The impacts of predation on lake sturgeon Acipenser fulvescens are not well understood. The objective of this study was to identify and quantify sources of predation that affect lake sturgeon eggs, larvae, and age‐0 juveniles in the Peshtigo River, Wisconsin, during 2006 and 2007. Egg bags were used to assess the rate of lake sturgeon egg co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
2
36
2
Order By: Relevance
“…Our results show that rates of predation on the juveniles by fish predators were low and similar to results documented by both Caroffino et al. () and French et al. ().…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that rates of predation on the juveniles by fish predators were low and similar to results documented by both Caroffino et al. () and French et al. ().…”
Section: Discussionsupporting
confidence: 92%
“…Less understood is the significant variation in larval success that can exist between sites on a single river or at a single sight over several years (Benson et al 2006;Kempinger 1988;LaHaye et al 1992). Nilo et al (1997), Verdon et al (2013), Shaw et al 2012, and Caroffino et al (2010a, 2010b found that year class strength is determined in the first few months of life by climate, hydrological conditions, and predation and is highly variable between years and sites. Duong et al (2011a) found that some of this variation could be explained by environmental variables, maternal effects, and spawning time.…”
Section: Larvaementioning
confidence: 99%
“…Lake sturgeon larvae are susceptible to predation by a variety of predator taxa, including fishes ) and crayfish (Crossman 2008). Research has quantified egg predation, but information on losses due to predation during the larval stage is lacking (Crossman 2008;Caroffino et al 2010b). Predation has been a major factor affecting recruitment of other sturgeon species (Parsley et al 2002;Steffenson et al 2015), and may be an important factor contributing to the lack of natural lake sturgeon recruitment.…”
Section: Introductionmentioning
confidence: 99%